Democracy is a good thing essays on politics, society, and culture in contemporary China - Yu, Keping (Thornton Center Chinese thinkers series., 2009)
"Presents selections of works of Yu Keping, a Chinese intellectual and figure in official think tanks, on politics and democracy that reveal the ongoing debates in Chinese political and intellectual circles on democratic reform and where China's political development is heading"--Provided by publisher.